Production and testing of wood-plastic composites boards from mixed particles of gmelina arborea and khaya ivorensis (2012)
"A lot of wood waste is generated from wood species in the Nigerian wood mills which are hazardous to the mill, mill workers and the wood. These wastes can be incorporated into plastic composites to manufacture value added products for interior and exterior applications in housing construction. This work examined the production and testing of plastic composites from mixed sawdusts of Gmelina arborea and Khaya ivorensis. Mixed sawdust of G.arborea and K. ivorensis collected from mills were screened, dried, milled to 0.4mm particle size, blended with polyvinylchloride (PVC) and chemical additives (calcium carbonate, talcum, calcium, magnesium and zinc stearate) in ratios 3:16:1;5:14:1 and 7:12:1. The mixes were extruded at barrel and die temperatures of 140oC and 165oC conditioned at temperature of 20oC and relative humidity of 55%. Specimens were cut from the products and tested for flexural and sorption properties in comparison with those of locally sourced commerical 100% PVC. The moduli of rupture and elasticity of the plastic composites were between 13.2 to 22.9 N/mm2 and 1254.0 to 3346.7 N/mm2 respectively as against 2.4N/mm2 and 902.0N/mm2 for 100% PVC while the impact strength ranged between 5.0 to 7.9 N/mm2 in comparison with 2.1N/mm2 for 100% PVC. The results obtained revealed that the flexural properties were superior to those of commercial 100% PVC and increased with increasing wood content. The plastic composites produced were dimensionally stable with low sorption rates and were suitable for moderately stressed interior and exterior purposes. "